Analysis of Student Teacher Ratios in Indonesian Public and Private Elementary Schools (2021 2024) - Antonius Totok Priyadi; Faisal Kananda; Marinu Waruwu; Siti Halidjah; Venny Karolina (Journal of General Education and Humanities, 2026)
Unequal teacher distribution remains a persistent challenge in Indonesia despite the implementation of national standards for student-teacher ratios. This study aims to analyze the trends and proportions of student-teacher ratios in public and private elementary schools across Indonesia and to examine teacher distribution patterns in Sanggau Regency as a regional context. Employing a quantitative descriptive comparative approach, the study utilizes secondary data from Statistics Indonesia (BPS) and the Basic Education Data System (Dapodik) from 2021 to 2024. The unit of analysis comprises 38 provinces in Indonesia and Sanggau Regency. Student teacher ratios were calculated and analyzed using trend and comparative analyses. The findings reveal that the ratio in public elementary schools steadily declined from 15.35 in 2021/2022 to 14.29 in 2024/2025, indicating improved teacher availability, whereas private schools exhibited fluctuating patterns, ranging from 15.87 to 16.07. Three provinces, DKI Jakarta, West Java, and Banten, consistently exceeded the national ideal standard, suggesting the need for targeted teacher redistribution policies in high-density regions. In Sanggau Regency, overall ratios improved, yet substantial disparities among sub-districts persisted. The novelty of this study lies in integrating national trend analysis with regional contextual analysis to provide a more comprehensive understanding of teacher distribution dynamics. These findings emphasize the importance of data-driven and region-specific policies to achieve equitable teacher allocation and improve the quality of basic education in Indonesia.